Peran Kepala Sekolah dalam Meningkatkan Kedisiplinan Siswa di SMK Darul Wustha Jerowaru - Suhaini; Izzuddin, Ahmad; Rasyidi, Abdul Haris (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2023)
Head school is one the most important component in increase quality education, which has not quite enough answer For advance the education he lead. Head quality school with various life school like discipline school, climate culture school, and decline behavior naughty participant educate Study aim for : 1) For know condition internal and external environment at SMK Darul Wustha Jerowaru , 2) For know roles and responsibilities head school in increase discipline students at SMK Darul Wustha Jerowaru, and also 3) For know strategies and methods head school in embed discipline for students at SMK Darul Wustha Jerowaru. Research type This is study qualitative with method descriptive analysis, in the data collection process, researchers use method observation, interview and documentation. The validity of the researcher's data use technique triangulation. Data analysis was performed with three stages ie from results observation, interview and documentation. Conclusion from study This are : 1) Conditions internal and external environment of SMK Darul Wustha jerowaru, have : a) Strength, such as : discipline in obey the rules school, shake hands when meet with his teachers, dressed neat, and follow activities implemented by the school like Imtaq, pray duha, gymnastics on the day Saturday and pray. b) Weaknesses, such as : students who do not obey rule school, students who do not use uniform in accordance with rules, no do assignments/homework as well exists students who are still go out enter during class time. c) Challenges, such as : the role of parents, development increasingly technology fast and caring public around. d) Probability, from challenge the at a time as opportunity for head school along with teachers 2) Roles and responsibilities head school in increase discipline student role Good Where Already work hard control whole activity students during activity Study teach, start from enter yard school, up to go home school. 3) Strategy and method head school in increase discipline student show that head school apply some of these strategies discipline level the presence of the teacher who teaches especially those who teach in the first hour, so on head school apply such as religious culture Salat duha every day so that expected capable give self awareness student.